IMPLEMENTASI DANA BKSM (BANTUAN KHUSUS SISWA MISKIN) PESERTA DIDIK DALAM MENANGGULANGI PUTUS SEKOLAH DI SMA NEGERI PLOSO JOMBANG - Hardiono Hardiono (Universitas Islam Lamongan, 2020)
Abstract :BKSM is a national program whose aim is to eliminate special obstacle for poor students inschooling participation by helping special poor students in getting the proper access of education service.T he receiver of BKSM fund which is managed by education and culture ministry are specialized for poor students and susceptible at grade school, Junior High School and Senior High School or state and private Vocational School which has fulfilled the requirements or criteria based on the technical guidelinie which is issued by the education and culture ministry.The approach used in this research is qualitative approach, which is divided into four steps. They are planning, implementation, data analysis and evaluation. For the technique of collecting data, the researcher applies some techniques of collecting data among others observation, interview, quisionaire and documentation.The researecher used purposive sampling which is based on the ability of the informan in describing about the implementation of BKSM fund in SMA Negeri Ploso Jombang clearly. Apart from that in presenting the result of the research, the researcher differentciate it into some steps. That is conducting research on informan characteristics, examine the economy condition of the students who receive the fund, find out the causes of the students who are threatened to quit school or school drop out and find out about the use of the fund. From the feedback and the result of research which have been done, the researcher knows the result of BKSM fund usage for poor students to prevent them from drop school so it can be concluded that, by the presence of BKSM fund students can get further education without any problem or barrier of school fee. Keywords: Special for poor students, drop out of school Abstrak :Program BKSM adalah Program Nasional yang bertujuan untuk menghilangkan halangan khusus siswa miskin dalam berpartisipasi bersekolah dengan membantu siswa khusus miskindalam memperoleh akses pelayanan pendidikan yang layak, Penerima dana BKSM yang dikelola oleh Kementerian Pendidikan dan Kebudayaan adalah khusus siswa miskin dan rentan pada Sekolah Dasar (SD), Sekolah Menengah Pertama (SMP), Sekolah Menengah Atas (SMA) atau Sekolah Menengah Kejuruan (SMK) negeri dan swasta yang telah memenuhi kriteria sesuai pedoman/petunjuk teknis yang dikeluarkan oleh Kementerian Pendidikan dan Kebudayaan.Pendekatan yang diambil dalam penelitian ini adalah pendekatan kualitatif yang dibagi dalam empat tahap yaitu perencanaan, pelaksanaan, analisis data, dan evaluasi. Dan untuk teknik pengumpulan data, peneliti menggunakan beberapa teknik pengumpulan data, antara lain : observasi, wawancara, kuisioner dan dokumentasi. Peneliti menggunakan sampel purposif (purposive sampling) yang didasarkan pada kemampuan informan menggambarkan secara jelas mengenai implementasi bantuan BKSM di SMA Negeri Ploso. Di samping itu untuk penyajian hasil penelitian dibedakan dalam beberapa tahapan yaitu melakukan penelitian mengenai karakteristik informan, meneliti gambaran ekonomi siswa penerima bantuan, mencari penyebab ancaman siswa putus sekolah, dan mencari tahu tentang pemanfaatan dana bantuan tersebut. Dari temuan dan hasil analisa penelitian yang dilakukan maka dapat diketahui hasil dari pemanfaatan dana BKSM yang dipergunakan khusus siswa miskin guna mencegah putus sekolah. Jadi dapat disimpulkan bahwa dengan adanya bantuan dana BKSM siswa dapat melanjutkan sekolah tanpa harus terhalang beban biaya sekolah. Kata kunci: Khusus Siswa Miskin, Putus Sekolah